2010
DOI: 10.3184/030823410x12857507693437
|View full text |Cite
|
Sign up to set email alerts
|

A Green and Efficient Synthesis of 1-Chloromethyl -2,3,4,5-Tetramethoxy-6-Methylbenzene

Abstract: The title compound, a key intermediate for preparing coenzyme Q analogues, was prepared in excellent yield by a reaction sequence starting from the commercially available 3,4,5-trimethoxybenzadehyde via Wolff-Kishner reduction, selective bromination, methoxylation and Blanc chloromethylation reaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…2, 3, 4, 5-Tetramethoxytoluene 4, 1-chloromethyl-2, 3, 4, 5-tetramethoxy-6-methylbenzene 5 and 2-chloromethyl-5, 6-dimethoxy-3-methyl- [1,4] …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…2, 3, 4, 5-Tetramethoxytoluene 4, 1-chloromethyl-2, 3, 4, 5-tetramethoxy-6-methylbenzene 5 and 2-chloromethyl-5, 6-dimethoxy-3-methyl- [1,4] …”
Section: Methodsmentioning
confidence: 99%
“…The metabolites of CoQ homologues, and a number of synthetic CoQ analogues ( Fig. 1) have been shown to be capable of inhibiting, activating, or occupying sites in the mitochondrial permeability transition pores [4][5][6][7][8][9][10]. Among the CoQ homologues, which have been synthesised previously, substituted benzoquinone derivatives bearing a heterocyclic substituent can be useful as blood platelet aggregation inhibitors, glycation inhibitors, vascular relaxants, and cardiovascular agents [9].…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…3,4 Although several methods for the preparation of N-benzylpiperazine have been reported, most of them employ the direct benzylation of piperazine or start from monoprotected N-acyl-and N-aroylpiperazines under carefully controlled basic conditions; however, these methods always produce a mixture of products from which N-benzylpiperazine (4) is difficult or impossible to isolate. 2-6 Therefore, a convenient and practical method for its synthesis is still a desirable goal and we now report a simple and efficient route for the preparation of 4 and also of 1-aralkyl-4-benzylpiperazine derivatives (7).…”
Section: A Convenient Synthesis Of Nbenzylpiperazine 1-aralkyl-4-benmentioning
confidence: 99%
“…CoQ 10 is also sold as a drug or dietary supplement in many countries, and there is an increasing market demand. Many researches [3][4][5][6][7][8][9][10][11][12][13][14] have shown that some metabolites of CoQ 10 , and a number of synthetic CoQ analogues exhibit significant biological activities, such as inhibition of mitochondrial complex I, lipid peroxidation activity and blood platelet aggregation. Especially, some CoQ analogues with heterocyclic substituents could be developed as drugs, [12][13][14][15] so to find a simple and efficient synthetic route for its preparation is considerable incentive.…”
Section: Introductionmentioning
confidence: 99%